1911 (Camden fifth series, 2016)
In the early afternoon I take E. to see Dr. Johnson's house – not very willingly because I have not wished her to form the worst impression of my intended purchase. Mr. Burr, agent for the Calthorpe estates, goes with us. Happily some attempt has been made by the care-taker to clean up the windows and sweep the house down a bit and it looks a little less dreary than when I saw it some weeks since.